Association between niacin intake and chronic kidney disease in male participants—a cross-sectional study from the NHANES (2005–2018) - Hu, Cong; Tang, Ting (Frontiers in Nutrition, 2025)
BackgroundChronic kidney disease (CKD), a significant health challenge in the United States, often progresses from asymptomatic conditions to advanced stages and exhibits a higher prevalence among male individuals. Niacin is known for its metabolic and antioxidant roles, potentially influencing CKD progression. The association between niacin intake and CKD has been rarely investigated in male participants.MethodsThis cross-sectional study utilized data of 13,946 male participants aged above 18 years from the National Health and Nutrition Examination Survey (NHANES) 2005–2018. CKD was diagnosed by albumin-to-creatinine ratio (ACR) and estimated glomerular filtration rate (eGFR). The niacin intake was recorded according to two 24-h dietary recalls. The association between niacin intake and CKD in male participants was examined using weighted logistic regression models, restricted cubic splines, and stratified analyses.ResultsThe prevalence of CKD was 17.07%. There was a prominent non-linear relationship between niacin intake and CKD (p-non-linear < 0.05). The inflection point for niacin intake was 26.79 mg (p for log-likelihood ratio < 0.05). The adjusted odds ratios (ORs) for the highest quartile of niacin intake and CKD were 0.752 (95% confidence interval [CI]: 0.591–0.959). In addition, race, body mass index (BMI), and cardiovascular disease (CVD) were significantly associated with this relationship (p for interaction < 0.05). However, poverty-to-income ratio (PIR), education level, smoking status, alcohol consumption, hypertension, and diabetes were not statistically significantly associated with the relationship between niacin intake and CKD in male patients (p for interaction > 0.05).ConclusionIn male patients, the niacin intake will reduce the risk of CKD.